2016
DOI: 10.1002/jmri.25353
|View full text |Cite
|
Sign up to set email alerts
|

Optimal high b-value for diffusion weighted MRI in diagnosing high risk prostate cancers in the peripheral zone

Abstract: 4 J. Magn. Reson. Imaging 2017;45:125-131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 37 publications
3
31
0
1
Order By: Relevance
“…Our results showed that this method could not improve the assessment of radiation‐induced changes in tumors. Recent studies suggested that high b‐values of 1400–2000 s/mm 2 were superior to detect prostate cancer than the standard b‐value of 1000 s/mm 2 . However, high b‐values above 1000 s/mm 2 revealed similar ADC ratios between the irradiated and nonirradiated regions as the b‐value of 800 s/mm 2 in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that this method could not improve the assessment of radiation‐induced changes in tumors. Recent studies suggested that high b‐values of 1400–2000 s/mm 2 were superior to detect prostate cancer than the standard b‐value of 1000 s/mm 2 . However, high b‐values above 1000 s/mm 2 revealed similar ADC ratios between the irradiated and nonirradiated regions as the b‐value of 800 s/mm 2 in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…The non-monoexponential nature of signal decays with b value in prostate tissues complicates comparisons between studies using different b value ranges [37]. However, our use of higher b-values may have had an impact on tumor conspicuity as supported by a recent study that demonstrated AUC for differentiating high risk PC from low risk PC increases with an increase in b-value, reaching maximum AUC at b=1600 s/mm [38]. Another possible explanation for the differences is that we performed a volumetric analysis of ADC values, as the lesion contouring was performed on multiple ADC slices to cover the entire tumor, enabling us to evaluate heterogeneous tumors with improved accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the existing literature, an increase in lesion-to-normal contrast and contrast-to-noise ratio compared to conventional ADC is only expected with acquired or computed DWI images at b-values higher than 1500 s/mm² [13,14,16,20,21]. cDWI images compared to original DWI images at the same b-value featured a reduced artifact level with similar or better CR and CNR values without additional acquisition time on top of the scan time used to obtain DWI with standard b-values [10,12,15,17,21].…”
Section: Discussionmentioning
confidence: 99%
“…Also Agarwar et al investigated the ability of cDWI to identify low-risk lesions based on DWI data. They analyzed cDWI data of 42 patients with b-values up to 4000 s/mm² and suggested cDWI with a b-value of 1600 -2000 s/mm² as a mean for the selection of active surveillance patients (maximum AUC of 0.75) [20].…”
Section: Discussionmentioning
confidence: 99%